Geometric morphometrics in ammonoids based on virtual modelling - Moron Alfonso, Daniel Andres (2021)
Linear morphometrics is the most widely applied technique to study the variationof the conch morphology in ammonoids and other ectocochleate cephalopods. However,because this method frequently relies upon a few linear measurements, it lacksthe explanatory power to accurately characterize the shape of the whorl cross-section,which is instead discussed solely in descriptive terms, e.g., elliptical, triangular, or subquadrate.Here, we introduce a landmark-based geometric morphometric approach tostudy ammonoid whorl cross-sections, derived from the regularly used morphometricparameters in cephalopods. This new technique uses virtual modelling to generatesemi-landmark configurations and virtual models of whorl cross-sections. We applied itto study 50 ammonoid specimens belonging to 48 genera exhibiting a wide range ofmorphologies and ages. Results indicate that this new method is appropriate todescribe the shape of ammonoid whorl cross-sections, allowing us to construct a morphospaceshowing several biological patterns (e.g., clustering and homeomorphy), andcomplex morphological transformations that, in some cases, correlate with evolutionarytendencies described by previous authors. Further, this technique can be used togenerate the basic segment required for the elaboration of the virtual models employedin hydrostatic and hydrodynamic studies.